Popular Music, Stars and Stardom - Loy, Stephen; Rickwood, Julie; Bennett, Samantha (ANU Press, 2018)
A popular fascination with fame and stardom has existed in Western culture since the late eighteenth century; a fascination that, in the twenty‑first century, reaches into almost every facet of public life. The pervasive nature of stardom in modern society demands study from the perspectives of a range of distinct but thematically connected disciplines. The exploration of intersections between broader considerations of stardom and the discourses of popular music studies is the genesis for this volume. The chapters collected here demonstrate the variety of work currently being undertaken in stardom studies by scholars in Australia. The contributions range from biographical considerations of the stars of popular music, contributions to critical discourses of stardom in the industry more broadly, and the various ways in which the use of astronomical metaphors, in both cultural commentary and academic discourse, demonstrate notions of stardom firmly embedded in popular music thought. Not only do these chapters represent a range of perspectives on popular music, stars and stardom, they provide eloquent and innovative contributions to the developing discourse on stardom in popular music.